Evaluation of two novel barcodes for species recognition of opportunistic pathogens in Fusarium. Issue 2 (February 2016) - Al-Hatmi, Abdullah M.S.; Van Den Ende, A.H.G. Gerrits; Stielow, J. Benjamin; Van Diepeningen, Anne D.; Seifert, Keith A.; McCormick, Wayne; Assabgui, Rafik; Gräfenhan, Tom; De Hoog, G. Sybren; Levesque, C. André
Abstract: The genus Fusarium includes more than 200 species of which 73 have been isolated from human infections. Fusarium species are opportunistic human pathogens with variable aetiology. Species determination is best made with the combined phylogeny of protein-coding genes such as elongation factor ( TEF1 ), RNA polymerase ( RPB2 ) and the partial β-tubulin ( BT2 ) gene. The internal transcribed spacers 1, 2 and 5.8S rRNA gene (ITS) have also been used, however, ITS cannot discriminate several closely related species and has nonorthologous copies in Fusarium . Currently, morphological approaches and tree-building methods are in use to define species and to discover hitherto undescribed species. Aftter a species is defined, DNA barcoding approaches can be used to identify species by the presence or absence of discrete nucleotide characters. We demonstrate the potential of two recently discovered DNA barcode loci, topoisomerase I ( TOP1 ) and phosphoglycerate kinase ( PGK ), in combination with other routinely used markers such as TEF1, in an analysis of 144 Fusarium strains belonging to 52 species. Our barcoding study using TOP1 and PKG provided concordance of molecular data with TEF1 . The currently accepted Fusarium species sampled were well supported in phylogenetic trees of both new markers.